Neoopricznina — Aleksander Dugin i Euroazjatycki Związek Młodzieży - Heizer, Paulina (Przegląd Rusycystyczny, 2012)
Paulina Heizer Wyższa Szkoła Europejska im. ks. J. Tischnera, Kraków, Poland pheizer@wse.krakow.pl Неоопричнина — Александр Дугин и Евразийский союз молодежи Резюме одной из самых серьезных проблем, которые встали перед российской Федерацией после падения Советского Союза, был отход от идеологии. попытка построения нового государства, опирающегося на отрицании коммунистической идеологии, оказалась неэффективной и недолговременной. ответом на идеологический кризис оказалась теория геополитики александра дугина, который использовал евразианстао, философскую мысль об исключительности россии как восьмого континента. дугин в 2003 г. основал новую организацию — евразийский союз молодежи, который, отсылая до времен ивана грозного, стал новой опричниной. она должна стоять на страже идеалов евроазиатства и привести к окончательной победе россии, единственной сокровищницы настоящей морали. NEOOPRICHNINA — ALEXANDER DUGIN AND EURASIAN YOUTH UNION Summary After the collapse of Soviet Union, Russian Federation suffered because of wide crisis. Ideologyб which suddenly disappearedб was one of the most serious problems. Alexander Dugin who was becoming more famous in that time, presented his concept of the new place of Russia in the international arena. This concept was based on the Russian philosophical thought from 1920’s which assumed that Russia is unique 8th continent. Dugin added to this concept geopolitical background. In 2003 he founded Eurasian Youth Union which he called neooprichnina and which is supposed to fight for his main ideas such as Conservative Revolution and so called the Project “Russia 3”. Both of this programs are strongly inter-related and serve the main idea to which Eurasia is the main protector of world values and has to win the eternal battle.